2017
DOI: 10.3747/co.24.3558
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Systemic Therapy in Breast Cancer: Use and Trends in Radiotherapy Practice

Abstract: BackgroundThe use of neoadjuvant systemic therapy (nast) in the treatment of breast cancer is increasing, and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Despite the several advantages of NAC for patients, several studies have shown very low existing rates NAC use in North America, with overall use of 20.2% in the US according to the National Cancer Database [ 11 ], and only 5% in a national Canadian study [ 12 ]. Interestingly, the recent reports during the COVID-19 pandemic have shown a significant rise in the use of neoadjuvant systemic therapy, both chemotherapy and endocrine therapy, within North America [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the several advantages of NAC for patients, several studies have shown very low existing rates NAC use in North America, with overall use of 20.2% in the US according to the National Cancer Database [ 11 ], and only 5% in a national Canadian study [ 12 ]. Interestingly, the recent reports during the COVID-19 pandemic have shown a significant rise in the use of neoadjuvant systemic therapy, both chemotherapy and endocrine therapy, within North America [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%